Extensive sonographic ulnar nerve enlargement above the medial epicondyle is a characteristic sign in Hansen's neuropathy. - Lokesh Bathala; Venkataramana N Krishnam; Hari Kishan Kumar; Vivekananda Neladimmanahally; Umashankar Nagaraju; Himanshu M Kumar; Johan A Telleman; Leo H Visser (Public Library of Science (PLoS), 2017)
Earlier studies have shown sonographic enlargement of the ulnar nerve in patients with Hansen's neuropathy. The present study was performed to determine whether sonography or electrophysiological studies can detect the specific site of ulnar nerve pathology in leprosy.Eighteen patients (thirty arms) with Hansen's disease and an ulnar neuropathy of whom 66% had borderline tuberculoid (BT), 27% lepromatous leprosy (LL) and 7% mid-borderline (BB) leprosy were included in the study. Cross-sectional area (CSA) of ulnar nerve was measured every two centimeters from wrist to medial epicondyle and from there to axilla. All patients underwent standard motor and sensory nerve conduction studies of the ulnar nerve. Thirty age and sex matched controls underwent similar ulnar nerve CSA measurements and conduction studies.Ulnar nerve was clinically palpable in 19 of the 30 arms of patients. Motor and sensory nerve conduction studies of the ulnar nerve showed a reduced compound motor action potential and sensory nerve action potential amplitude in all patients. Motor Conduction Velocity (MCV) in patients were slower in comparison to controls, especially at the elbow and upper arm, but unable to exactly locate the site of the lesion. In comparison to controls the ulnar nerveCSA was larger in the whole arm in patients and quite specific the maximum enlargement was seen between nulnar sulcus and axilla, peaking at four centimeters above the sulcus.A unique sonographic pattern of nerve enlargement is noted in patients with ulnar neuropathy due to Hansen's disease, while this was not the case for the technique used until now, the electrodiagnostic testing. The enlargement starts at ulnar sulcus and is maximum four centimeters above the medial epicondyle and starts reducing further along the tract. This characteristic finding can help especially in diagnosing pure neuritic type of Hansen's disease, in which skin lesions are absent, and alsoto differentiate leprosy from other neuropathies in which nerve enlargement can occur.